Nicaragua : Staff Report for the 2002 Article IV Consultation and Requests for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility and for Interim Assistance Under the Enhanced Initiative for Heavily Indebted Poor Countries. (IMF Staff Country Reports; Country Report ;, 2003)
This paper assesses Nicaragua's 2002 Article IV Consultation and Requests for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF) and for Interim Assistance Under the Enhanced Initiative for Heavily Indebted Poor Countries (HIPC). A key program objective is medium-term fiscal sustainability. This will require a significant reduction of primary spending, while protecting poverty-reducing outlays, and an increase in tax revenues. The IMF staff recommends that the authorities' request for a new three-year PRGF arrangement and interim HIPC assistance be approved.